Evaluation of Funding Gastroenterology Research in Canada Illustrates the Beneficial Role of Partnerships - Philip M Sherman; Kimberly Banks Hart; Keeley Rose; Kwadwo Bosompra; Christopher Manuel; Paul Belanger; Sandra Daniels; Paul Sinclair; Stephen Vanner; André G Buret (Canadian Journal of Gastroenterology)
BACKGROUND: Funders of health research in Canada seek to determine how their funding programs impact research capacity and knowledge creation.